Spontaneous bilateral vertebral artery dissection complicated by hemodynamic posterior circulation stroke: A case report - Adam Sqalli Houssaini, MD; Sarah Lembarki, MD; Fatima Chait, MD; Mohamed Jiddane, PhD; Firdaous Touarsa, PhD (Radiology Case Reports, 2025)
Bilateral vertebral artery dissections account for only 8% of all vertebral artery dissections and cause just 2% of all ischemic strokes. They can occur spontaneously, even without any triggering factor. Classical clinical findings, such as headache or neck pain, may be absent, particularly in the context of a stroke. Imaging is the modality of choice for diagnosis and includes ultrasound, catheter-based DSA, computed tomography angiography, and MRA. The main differential diagnoses include atherosclerotic plaques, hypoplastic vertebral artery, and vertebral artery fenestration. The primary treatment involves antithrombotic therapy. We report the case of a 57-year-old woman with no history of cardiovascular disease who presented to the emergency department with hemibody weakness and slurred speech. Magnetic resonance imaging on admission revealed multiple hypoperfusion-related ischemic areas involving the vertebrobasilar artery territory and findings suggestive of bilateral vertebral artery dissection.